The Development of Textbook For A Course of Pengembangan Bahan Ajar Biologi (Biology Teaching Material Development) For Biology Education Department Students of Universitas Ahmad Dahlan - Hani Irawati (Universitas Tidar, 2019)
The aim of this research is to develop a textbook for a course of pengembangan bahan ajar biologi (Biology teaching material development) for the students of biology education department, Faculty of Education and Teachers Training, Universitas Ahmad Dahlan. This research is a Research and Development (R & D). The development was done by referring to a 4-D model which includes define, design, develop, and disseminate. The assessment of the product was conducted by the expert of the material and the expert of the media. The trial was done by 47 students of biology education department, Faculty of Education and Teachers Training, Universitas Ahmad Dahlan. In detail, there are 10 students for the small group trial and 37 students for the field trial. The data was collected using questionnaires. The data which was obtained from the questionnaires were analysed descriptively. The finding of the research is as follows; 1). The textbook is suitable to be used in the learning process, 2). The developed textbook was assessed by (a) the aspect of content advisability belongs to good quality, (b) the aspect of presentation belongs to good quality (c) the aspect of language belongs to very good quality, and (d) the aspect of graphics belongs to good quality, 3). The students’ responses toward the developed textbook which is categorized as “good” in terms of both the aspect of the look and the aspect of the material presentation. While the aspect of benefit is categorized as “very well”.